An essay on trade and transformation - Linder, Staffan Burenstam (Uppsala : Almqvist & Wiksell Boktr, 1961)
This study will deal only with the welfare and structural aspects of international trade..
Bibliography: p. 154-160.
gau 27/02/17
Loans
Keywords: Commerce; Commercial policy; Welfare economics; Economic development